The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acs.est.8b04858
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency of Capacitive Deionization

Abstract: Capacitive deionization (CDI) as a class of electrochemical desalination has attracted fast-growing research interest in recent years. A significant part of this growing interest is arguably attributable to the premise that CDI is energy efficient and has the potential to outcompete other conventional desalination technologies. In this review, systematic evaluation of literature data reveals that while the absolute energy consumption of CDI is in general low, most existing CDI systems achieve limited energy ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
145
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(147 citation statements)
references
References 100 publications
2
145
0
Order By: Relevance
“…The thermodynamic energy efficiency, in contrast, is a metric which is appropriate for any desalination method, allowing for the performance of CDI to be placed in context with other technologies. 100,101 Nonetheless, very few studies have reported the thermodynamic energy efficiency of CDI, thus propagating the notion that CDI, with improved electrode materials, can become an energy efficient desalination technology.…”
Section: Electro-driven Desalination: Capacitive Deionizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermodynamic energy efficiency, in contrast, is a metric which is appropriate for any desalination method, allowing for the performance of CDI to be placed in context with other technologies. 100,101 Nonetheless, very few studies have reported the thermodynamic energy efficiency of CDI, thus propagating the notion that CDI, with improved electrode materials, can become an energy efficient desalination technology.…”
Section: Electro-driven Desalination: Capacitive Deionizationmentioning
confidence: 99%
“…During the charging step of CDI, irreversible energy losses from parasitic side reactions, ion transport resistances (in the spacer channel and electrodes), and electronic resistances (electrode matrix, membranes, current collector, contacts) are inevitable, allowing for only a fraction of the supplied energy to be stored for potential recovery. 101 In the discharging stage, similar losses prevent complete recovery of the energy that is stored. Though decreasing the extent of salt removal and current density can reduce the magnitude of irreversible losses-allowing for a greater portion of energy to be recovered-achieving a near ideal reversible CDI process would necessitate infinitely long cycle times.…”
Section: Electro-driven Desalinationmentioning
confidence: 99%
“…However, the capital investments, operating costs, and energy consumption are still high. Capacitive deionization (CDI) has been proposed as an energy‐saving and economic deionization approach . However, the removal capacity of a conventional CDI device remains very low owing to the limited ion electrosorption capacity of carbon electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…Since the charge efficiency shows the degree of electric charge utilized to remove the ions, it is a major index to determine the presence of parasite reactions as well as energy consumption [40]. The energy consumption in kT is the thermodynamic energy consumption based on the specific Gibbs free energy of separation, offering the scientific evidence to compare the energy efficiency of CDI systems with that of other desalination technologies [41].…”
Section: Standard Analysis Metricsmentioning
confidence: 99%